2020
DOI: 10.3389/fpsyt.2019.00952
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Cluster Randomized Controlled Trial of Individual Placement and Support (IPS) for Patients With Offending Histories

Abstract: Objective: To examine the feasibility of conducting a fully powered randomized controlled trial (RCT) of Individual Placement and Support (IPS). IPS is a form of supported employment which aims to put people into open employment quickly and in accordance with their preferences. It is delivered by employment specialists collocated within clinical teams, and provides time unlimited support for the individual and their employer, along with welfare benefits counselling.Method: A feasibility cluster RCT of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 44 publications
0
5
0
13
Order By: Relevance
“…Meta-analyses and reviews show that IPS is superior to traditional vocational rehabilitation in terms of achieving competitive employment and with regard to multiple other vocational outcomes like job tenure and total income [ 10 , 11 ]. This holds also true in specific groups like people diagnosed with a psychotic illness [ 12 ], patients with offending histories [ 13 ], or young adults [ 14 ]. All of the previous trials were conducted outside of Germany, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses and reviews show that IPS is superior to traditional vocational rehabilitation in terms of achieving competitive employment and with regard to multiple other vocational outcomes like job tenure and total income [ 10 , 11 ]. This holds also true in specific groups like people diagnosed with a psychotic illness [ 12 ], patients with offending histories [ 13 ], or young adults [ 14 ]. All of the previous trials were conducted outside of Germany, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed the quality of these economic studies using the CHEERS checklist; 41 had quality scores above 50%, including 24 with quality scores over 70%. Twelve studies that scored 70% or more on quality focused on IPS, were linked to RCTs, and concluded that it was cost-effective [17,18,20,25,30,31,[33][34][35][36][41][42][43]. Only two IPS studies were from the USA [30,36]; most IPS [3,18,20,23,31,41,51,56], where IPS services have been implemented and there is good access to welfare and health registry data to follow-up service users.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, six studies reported cost per QALY gained, (five favourable to SE/IPS), eight NMBs (all positive), four ROI (three positive) and 13 cost per employment outcome (nine favourable, three inconclusive, one negative). 18 studies included impacts on health outcomes and/or service utilisation, as well employment [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Table 2 shows 16 of these 23 studies had a short timeframe (maximum two years) [17-21, 23, 24, 26-29, 32, 33, 35-37], but there is growing evidence on longer-term economic impacts [22,25,30,31,34,[38][39][40].…”
Section: Ipsmentioning
confidence: 99%
See 2 more Smart Citations